Prognostic Value of Tissue Oxygen Saturation Using a Vascular Occlusion Test in Patients in the Early Phase of Multiorgan Dysfunction Syndrome. Issue 6 (June 2019) - Haertel, Franz; Reisberg, Diana; Peters, Martin; Nuding, Sebastian; Schroeder, Jochen; Werdan, Karl; Ebelt, Henning
ABSTRACT: Background: Multiple organ dysfunction syndrome (MODS) is a common disease pattern in intensive care units which is associated with an increased mortality. The aim of this study was to investigate whether a near-infrared spectroscopy (NIRS)-based noninvasive ischemia–reperfusion test (vascular occlusion test) using the parameter of tissue oxygen saturation (StO2 ) contains prognostic information for patients in the early phase of MODS. Methods: Within a period of 18 months between 2010 and 2012, 56 patients who newly developed MODS (⩽24 h after diagnosis, Acute Physiology and Chronic Health Evaluation [APACHE] II score ≥20, subgroups: cardiogenic MODS [cMODS] and septic MODS [sMODS]) were included into the study. The StO2 was determined non-invasively in the area of the thenar muscles using a bedside NIRS device, InSpectra Tissue Spectrometer Model 650 (Hutchinson Technology Inc., Hutchinson, MN). The VOT was carried out by inflating a blood pressure cuff on the upper arm 30 mmHg above systolic blood pressure for 5 min. The parameters occlusion slope (OS) and recovery slope (RS) were recorded. Results: Fifteen patients with cMODS and 41 patients with sMODS were included in the study (age: 62.5 ± 14.4 years, 40 men and 16 women, APACHE II score: 34.6 ± 6.4). Twenty-eight-day-mortality was 55.4% (cMODS: 7 out of 15 patients, sMODS: 24 out of 41 patients). The measurement of StO2 while applying the VOT at baseline showed an OS of −11.7 ± 3.7%/min and an RS of 2.2 ± 1.5%/s. Survivors had significantly better values compared with non-survivors at baseline regarding OS (−12.8 ± 3.5%/min vs. −9.8 ± 3.4%/min; P  = 0.016) and RS (2.6 ± 1.7%/s vs. 1.6 ± 1.0%/s; P  = 0.022). Receiver-operating characteristic (ROC) curves show that the area under the curve (AUC) for OS was found to be significantly related to 28-day mortality (AUC: 0.7; 95% confidence interval [CI]: 0.56–0.85; P  = 0.01). However, using both univariate and multivariate binary logistic regression models, RS was significantly associated with increased 28-day mortality (OR [univariate model]: 1.21 [95% CI: 1.1–1.8]; OR [multivariate model]: 1.23 [95% CI: 1.1–1.3]). Conclusions: Impaired values of the VOT-parameters OS and RS are associated with an increased 28-day mortality in patients in the early phase of MODS.